Hackerspaces, contexto capacitante e Ba - Santos, Otávio Carneiro dos (2018)
Hackerspaces are physical spaces maintained by communities for experimentation, knowledge creation and sharing. This research aims to identify if these spaces contain the features of favorable enabling contexts or ba. The methods used were a literature review about enabling contexts and a content analysis research over web pages of active hackerspaces all over the world as available in January 2017. A survey was conducted in September 2017 in order to complement the previous analysis. The findings show that even spread along many countries and continents, hackerspaces still keep common features among each other such as the focus on social events organization and project execution. The research concludes that there is evidence that hackerspaces possess the main features expected for ba and therefore are potentially suitable for knowledge creation and sharing.